2020
DOI: 10.1002/ijfe.2082
|View full text |Cite
|
Sign up to set email alerts
|

Does export upgrading really matter to economic growth? Evidence from panel data for high‐, middle‐ and low‐income countries

Abstract: The main objective of this study is to examine the long‐run relationship between export upgrading and economic growth for 67 countries over the period of 1984–2013. For this purpose, a panel cointegration framework that allows to control for parameters heterogeneity, cross‐sectional dependence and non‐stationarity has been deployed. Empirical results yield evidence of a positive and significant effect of export upgrading on economic growth for the full‐sample and high‐income panels, while this effect is negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 100 publications
(174 reference statements)
1
8
0
Order By: Relevance
“…However, our results are still comparable to recent empirical studies. For example, Koch (2021) finds that a 10% increase in export complexity leads to a 0.21% increase in real GDP per capita growth rate, while Chakroun et al. (2021) find that a 10% increase in export upgrading increases growth rates by 0.30%.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, our results are still comparable to recent empirical studies. For example, Koch (2021) finds that a 10% increase in export complexity leads to a 0.21% increase in real GDP per capita growth rate, while Chakroun et al. (2021) find that a 10% increase in export upgrading increases growth rates by 0.30%.…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that high income countries benefit more from export upgrading as they have larger endowments in physical and human capital to fully exploit technological knowledge spillovers by having a larger absorptive capacity (Chakroun et al. , 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations